Naming God Together: Muslim-Christian Theology of Mercy in the Indonesian Context - Albertus Bagus Laksana (Journal of Asian Orientation in Theology, 2019)
Using the method of the new comparative theology, this essay attempts to take the Indonesian context seriously, where the recent and highly divisive religio-political tension has given rise as well to an inclusive public theological discussion of God as the Merciful, and offers an explicit comparative theological analysis of God as Merciful in the Muslim and Christian (Catholic) traditions. On the structural level, these two traditions agree that Mercy has at least three dimensions, namely ontological (mercy belongs to the very being of God), personal (Gods mercy is made manifest in paradigmatic human person) and social (mercy has a dynamic of reaching out to others in solidarity). While being formulated and expressed within the confines of each theological system, mercy as Gods quality is shown to be at the center of Muslim and Christian naming of God. The two traditions move from philosophical theism to thepersonal and social dimensions of manifesting Gods mercy in the world. This comparative theological analysis of God as the Merciful will serve as a responsible public theology in the complex and pluralistic Indonesian society.